Suffering in the land of sunshine : a Los Angeles illness narrative - Abel, Emily K. (Critical issues in health and medicine., 2006)
Following the end of World War II, it was widely reported by the media that Jewish refugees found lives filled with opportunity and happiness in America. However, for most of the 140,000 Jewish Displaced Persons (DPs) who immigrated to the United States from Europe in the years between 1946 and 1954, it was a much more complicated story. Case Closed challenges the prevailing optimistic perception of the lives of Holocaust survivors in postwar America by scrutinizing their first years through the eyes of those who lived it. The facts brought forth in this book are supported by case files record.